Occupation and bladder cancer in a hospital-based case–control study in Spain. Issue 5 (19th October 2007) - Samanic, C M; Kogevinas, M; Silverman, D T; Tardón, A; Serra, C; Malats, N; Real, F X; Carrato, A; García-Closas, R; Sala, M; Lloreta, J; Rothman, N; et al.
Abstract : Objectives: We investigated the association between occupation and bladder cancer in a hospital-based case–control study conducted in Spain. Methods: 1219 patients with transitional cell carcinoma of the urinary bladder and 1271 controls selected from 18 hospitals in Spain between June 1998 and September 2000 provided detailed information on life-time occupational history, smoking habits, medical history, and other factors. We used unconditional logistic regression to calculate odds ratios (OR) and 95% confidence intervals (CI) for each occupation and industry, adjusting for age, hospital region, smoking duration, and employment in a high-risk occupation for bladder cancer. Results: Statistically significant increased risks were observed among men employed as machine operators in the printing industry (OR 5.4; 95% CI 1.6 to 17.7), among men employed in the transportation equipment industry (OR 1.6; 95% CI 1.1 to 2.6) and among those who had worked for ⩾10 years in the electrical/gas/sanitary services (OR 3.9; 95% CI 1.5 to 10.4) and in hotels and other lodgings (OR 3.1; 95% CI 1.3 to 7.3). Men who worked as miscellaneous mechanics and repairers (OR 2.0; 95% CI 1.1 to 3.6) and as supervisors in production occupations (OR 2.1; 95% CI 1.2 to 3.6) also had excess risks for bladder cancer. Male farmers and those who worked in crop and livestock production had decreased risks for bladder cancer. We found no significant associations between occupation or industry and bladder cancer risk among women. Conclusions: We did not observe excess bladder cancer risk for many of the occupations identified as being a priori at high risk. Examination of more detailed job exposure information should help clarify these associations.